The gothic : a very short introduction - Groom, Nick (Oxford : Oxford University Press, 2012)
The Gothic is wildly diverse. It can refer to ecclesiastical architecture, supernatural fiction, cult horror films, and a distinctive style of rock music. It has influenced political theorists and social reformers, as well as Victorian home décor and contemporary fashion. This Very Short Introduction captures the history of the Gothic from ancient times to the present. It covers the sack of Rome by the barbarian tribes, mediaeval architecture, popular culture in the sixteenth century (including ballads and Revenge Tragedy), political theories of the seventeenth and eighteenth centuries, the rise of the Gothic novel, the Victorian Gothic Revival, and the influence of Gothic culture on film, music, and fashion. It includes familiar Gothic novels such Frankenstein and Dracula, while also covering Gothic gardening, slasher movies, and the current Goth scene. It is the only account of the Gothic that describes the entire history of the term, presenting it in all its richly complex and perversely contradictory glory.
Preface : a history of the gothic in thirteen chapters -- Origins of the Goths -- The ascent to heaven -- The iconoclasts -- The revenge of the dead -- Liberty gothic -- Gothic whiggery -- The sixties -- The descent into hell -- The poetics of blood -- The gothic dream -- New England Goths -- The ghost in the machine -- First and last and always.
Includes bibliographical references (p. 145-153) and index.
Keywords: ART, GOTHIC; GOTH CULTURE (SUBCULTURE); HORROR TALES, ENGLISH -- HISTORY AND CRITICISM